Wood composites materials, manufacturing, and engineering - Aguilera, Alfredo, 1964-; Davim, J. Paulo (Advanced composites ;, 2017)
Wood composites as part of wood engineering materials has been reaching a constant developing trend, being used on a wide range of applications and becoming worldwide as a very promising alternate material face to traditional building materials such as concrete, metal and plastics. In this part of the series are treated aspects among which advances functionalities in laminates, the activation of natural fibres, the natural matrix, and others industrials manufacturing research advances for wood material as composite.